THE INFLUENCE OF ENTREPRENEURIAL EDUCATION ON ENTREPRENEURIAL INTENTIONS BY THE MEDIATION OF SELF EFFICACY: STUDY OF A VOCATIONAL SCHOOL - Jurry Hatammimi; Devi Rosniawati (SEAN Institute, 2023)
Despite the low ratio between the total population and the number of businesses, Indonesia has a huge possibility to develop entrepreneurs in the digital age. Implementing the Vocational School 4.0 competency curriculum, which focuses on fostering the entrepreneurial aim of vocational students, is one method to improve this situation. However, this program hasn't yet been able to yield any notable outcomes. With self-efficacy serving as the mediating variable, this study aims to evaluate the impact of entrepreneurship education on the entrepreneurial intention of students majoring in online business and marketing at a state vocational school. The study employs a quantitative methodology, and the eleventh and twelfth grades were given online questionnaires to complete. In the meanwhile, a structural equation model and partial least squares are used to analyze the data. The findings of this study show that entrepreneurship education positively and significantly affects entrepreneurial intention and entrepreneurial self-efficacy, entrepreneurial self-efficacy positively and significantly affects entrepreneurial intention, and entrepreneurial self-efficacy mediates entrepreneurship education and entrepreneurial intention. It is advised to undertake a qualitative analysis to identify the most important aspects of entrepreneurial education, entrepreneurial intention, and entrepreneurial self-efficacy for further research.